PENGARUH REPUTASI ORGANISASI, UKURAN ORGANISASI, OPINI AUDIT DAN UKURAN KAP TERHADAP KINERJA ORGANISASI NIRLABA DI INDONESIA - Ika Kristianti; Nika Ardian (Jurnal Ilmu Manajemen, 2022)
The non-profit organisation positively impacts economic, reform, and social improvement. One of the non-profit organisations is the foundation. This study aims to analyse the effect of organisational reputation, organisational size, audit opinion and public accounting firm size on the performance of non-profit organisations. This research is quantitative. The sample in this study consisted of 80 foundations for 4 years of observation. The results show that organisational reputation does not affect the performance of non-profit organisations. Organisational size affects the performance of non-profit organisations. Audit opinion does not affect the performance of non-profit organisations, and the size of public accounting firms does not affect the performance of non-profit organisations. This study implies that the availability of sufficient total assets can provide opportunities for non-profit organisations to continue to improve and improve their performance.